Effects of Red Mud Addition in the Microstructure, Durability and Mechanical Performance of Cement Mortars - José Marcos Ortega; Marta Cabeza; Antonio José Tenza-Abril; Teresa Real-Herraiz; Miguel Ángel Climent; Isidro Sánchez (Applied Sciences, 2019)
Recently, there has been a great effort to incorporate industrial waste into cement-based materials to reach a more sustainable cement industry. In this regard, the Bayer process of obtaining alumina from bauxite generates huge amounts of waste called red mud. Few research articles have pointed out the possibility that red mud has pozzolanic activity. In view of that, the objective of this research is to analyse the short-term effects in the pore structure, mechanical performance and durability of mortars which incorporate up to 20% of red mud as a clinker replacement. As a reference, ordinary Portland cement and fly ash Portland cement mortars were also studied. The microstructure was characterised through mercury intrusion porosimetry and non-destructive impedance spectroscopy, which has not previously been used for studying the pore network evolution of red mud cement-based materials. The possible pozzolanic activity of red mud has been checked using differential scanning calorimetry. The non-steady state chloride migration coefficient and the mechanical properties were studied too. According to the results obtained, the addition of red mud entailed a greater microstructure refinement of the mortar, did not worsen the resistance against chloride ingress and reduced the compressive strength compared to control binders.